The effect of immunization of mice with blood stage parasite against Plasmodium berghei infection - Mahardika Agus Wijayanti Mahardika Agus Wijayanti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Immunity against malarial infection is a very complex molecular and cellular interaction and represents a combination of both humoral and cell mediated mechanism. However, which mechanism contributes to the protection effect is still not clear. Immunization against Plasmodium berghei infection represents a suitable malarial model to study the host immune responses against malarial infection. The present study was aimed at evaluating the effect of immunization of Swiss mice challenged with P. berghei on the blast transformation, prepatent period, parasitemia and mortality of the host. The result showed that P. berghei infection in .Swiss mice was acute and fatal. All non-immunized mice died following challenge with 1 x 108 parasite on day 8 -10 post infection. Blast transformation of splenic lymphocyte was higher in immunized mice than in non-immunized mice. Immunization with P. berghei and adjuvant in Swiss mice could evoke partial immunity to homolog parasite. Longer prepatent period, reduced parasitemia and decreased mortality were observed in this group. Eighty percent of immunized mice survived from P. berghei infection.Key Words : malarial immunity - immunization - blast transformation - prepatent period - parasitemia -mortality